ANALYSIS OF THE INFLUENCE OF PHOTOGRAMMETRY MARKETING IMPLEMENTATION, INTERNAL COORDINATION AND EXTERNAL POLICIES ON MONTHLY CERTIFICATE TIME PERFORMANCE BASED ON THE DECISION OF THE TOLL ROAD EARTHWORKS PROJECT MANAGER - Risky Setiawan; Agus Suroso (Pena Cendekia Insani, 2025)
Earthwork activities in toll road construction require accurate volume calculations and effective coordination so that Monthly Certificates can be issued on time. This study aims to analyze the influence of photogrammetry implementation, internal coordination, and external policies on project manager decision-making, and their impact on the time performance of Monthly Certificates. The research approach used is quantitative with regression analysis method. The results show that the implementation of photogrammetry, internal coordination, and external policies together have a positive influence on project manager decision-making, with external policies being the most dominant factor. Furthermore, project manager decision-making is proven to have a positive influence on the time performance of Monthly Certificates. These findings confirm that appropriate technological support, effective internal coordination, and clear external policies can improve the quality of project manager decision-making, which ultimately contributes to the acceleration of the preparation and issuance of Monthly Certificates in toll road earthworks.